223k views
0 votes
Solve for y.
(4y + 5) (-2y + 3) = -3-7y - 8y2 +9y - 9

Solve for y. (4y + 5) (-2y + 3) = -3-7y - 8y2 +9y - 9-example-1
User Jureispro
by
5.3k points

2 Answers

3 votes

Answer:


(4y + 5)( - 2y + 3) =-3 -7y - 8 {y}^(2)+9y - 9 \\ - 8 {y}^(2) + 12y - 10y + 15 = - 12 + 2y - 8 {y}^(2) \\ - 8 {y}^(2) + 2y + 15 = - 12 + 2y - 8 {y}^(2)

value of y is getting cancelled out

so value of y does not exist.

User Statikuz
by
5.5k points
6 votes

Explanation:

hope this will help you......

Solve for y. (4y + 5) (-2y + 3) = -3-7y - 8y2 +9y - 9-example-1
User Edi Wang
by
5.3k points